Electrochemical promotion of methane oxidation on Pd nanoparticles deposited on YSZ. (2018) - Kalaitzidou, I.; Zagoraios, D.; Brosda, S.; Katsaounis, A.; Vernoux, P.; Vayenas, C.G.
Abstract: Studies on CH4 oxidation are of special interest due to the difficulty in activating this particular hydrocarbon, due to the demand of an active catalyst at low temperatures (T50 at 300°C) as well as due to possible deactivation of the catalyst upon exposure at high temperatures [1]. To address these issues, we used Electrochemical Promotion of Catalysis (EPOC), which was discovered in the early 80's and has been studied for more than 100 catalytic systems [2]. EPOC allows for the controlled enhancement of the catalytic activity by potential or small current application between a catalyst (working electrode) supported on a solid electrolyte and an auxiliary electrode. In this study, Pd nanoparticles (2-4 nm) deposited on O 2- conductor (YSZ) was used to study the electrochemical promotion of methane oxidation. It was found that EPOC could be used to promote nanodispersed catalysts and enhance the reaction rate at temperatures lower than those that have been observed in previous studies [3, 4]